Agent-Based Reporting for Flood Emergency Operation Center - Noor Suziane, Samsudin (2004)

(untitled)
Flood Emergency Operation Centre (EOC) caters for multi-organization function. Currently, problems exist in flood reporting system during emergeny condition such as duplications and non-standardized reporting format among agencies involved. Through knowledge acquisition, these problems and requirements were identified based on conducted interviews and document reviews. This study explores an agent application as a solution for flood EOC reporting. A prototype was developed using the web-based programming languages, Active Server Page (ASP) linked with MsAccess database for an auto-generating reporting agent-based system. The purpose of this prototype is to standardize the flood-reporting format that can be monitored locally or from remote location.